Ertty System®: distalização segmentar - Meloti, Aparecida Fernanda [UNESP]; Silva, Ertty; Pinho, Sérgio; Gandini Júnior, Luiz Gonzaga [UNESP]; Santos Pinto, Ary dos [UNESP] (My University, 2012)
Introduction: Ertty System® is an intraoral system of biomechanical forces to move teeth anteroposteriorly. The application of forces on this system results in the distalization of the molar and all lateral segment in the side to be distalized, including premolars and canine, resulting in alveolar bone remodeling. This system is indicated to correct uni- or bilateral maxillary dental Class II malocclusion in permanent dentition both in children and adults. It is contraindicated in case of skeletal asymmetries, protrusion of maxillary and mandibular teeth, skeletal Class II and Class II subdivision malocclusions with mandibular midline deviation. This study describes Ertty System® and presents two clinical cases treated using this system. The two female patients presented with Class II malocclusion subdivision and maxillary midline deviation. Results: It was achieved correct alignment and leveling, Class I dental relation and correction of upper midline. Conclusion: The success and stability of results confirmed diagnosis and treatment adequacy.

Introdução: o Ertty System® é um sistema intrabucal de forças biomecânicas para movimentação dentária no sentido anteroposterior. A aplicação de forças do sistema resulta na distalização do molar e de todo o segmento lateral do lado a ser distalizado, incluindo pré-molares e canino, com consequente remodelação óssea alveolar. O sistema é indicado para correção da má oclusão de Classe II dentária maxilar em dentição permanente, uni- ou bilateral, tanto em pacientes jovens quanto em adultos. É contraindicado em caso de assimetrias esqueléticas, biprotrusão dentária, Classe II esquelética e Classe II subdivisão com desvio da linha média dentária inferior. O objetivo deste trabalho foi descrever o Ertty System ® e apresentar dois casos clínicos de pacientes com má oclusão de Classe II, subdivisão, e desvio da linha média dentária superior tratados com esse sistema. Resultado: obteve-se um correto alinhamento e nivelamento, relação dentária de Classe I e correção da linha média superior. Conclusão: o sucesso e a estabilidade dos resultados confirmaram o correto diagnóstico e tratamento.
Ertty System®: Segment distalization
Keywords: Angle Class II malocclusion; Orthodontic appliances; Temporomandibular joint; Má oclusão Classe II de Angle; Aparelhos ortodônticos; Articulação temporomandibular